Pemberdayaan Kesehatan Masyarakat Dusun Kemantren II Semawung Melalui Edukasi Pengelolaan Obat - Hendra, Phebe; Riswanto, Florentinus Dika Octa; Setyani, Wahyuning; Julianus, Jeffry; Rajagukguk, ⁠Greysianita; Santi , Nyoman Pradnya Yoni Meytri; Bramantyo , Dominicus Adyatma; Siallagan , Angela Meirella; Putri , Elsha Tiany (Rengganis Jurnal Pengabdian Masyarakat, 2025)
The misuse of drugs is a major health issue in Indonesia, largely due to a lack of understanding about proper drug management. Knowledge of correct medication use is essential to prevent administration errors. Key issues in Dusun Kemantren II, Semawung Village include a limited understanding of medication usage and inadequate drug storage systems. Engaging the community with information on effective drug management is essential to address this. This community service initiative aims to improve drug management knowledge in Dusun Kemantren II, Semawung Village, Purworejo District. The activity was carried out on May 4, 2025, with 23 participants. Evaluation results showed increased participants' knowledge after the education, based on average pre-test and post-test scores. This program successfully improved public knowledge and awareness regarding the importance of proper drug management. It provided practical means, such as medicine boxes, to support the implementation of this knowledge at the household level.